The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/e20060471
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Node Similarity Learning for Community Detection in Attributed Networks

Abstract: Attributed networks consist of not only a network structure but also node attributes. Most existing community detection algorithms only focus on network structures and ignore node attributes, which are also important. Although some algorithms using both node attributes and network structure information have been proposed in recent years, the complex hierarchical coupling relationships within and between attributes, nodes and network structure have not been considered. Such hierarchical couplings are driving fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Data sets : in order to test the performance of our method, we selected three networks with node attributes: the counselor relationship network (Consult) [ 15 ], the London gang relationship network (London Gang) [ 55 ] and the Montreal gang relationship network (Montreal Gang) [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data sets : in order to test the performance of our method, we selected three networks with node attributes: the counselor relationship network (Consult) [ 15 ], the London gang relationship network (London Gang) [ 55 ] and the Montreal gang relationship network (Montreal Gang) [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Related work of community detection on attributed networks. The attributed network (or attributed graph) [ 15 , 46 ] is a kind of important complex network, which has both topological structures and node attributes. In the attributed network context, the topological structure represents the interactions between nodes and the attributes describe the inherent characteristics of each node in the network.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…By combining the characteristics of network structure with node attributes, Meng et al [11] propose a novel coupled node similarity (CNS) measure to capture both explicit and implicit interactions between nodes in their paper "Coupled node similarity learning for community detection in attributed networks". CNS is used to generate the edge weights and then transfer a plain graph to a weighted graph.…”
Section: Complex Networkmentioning
confidence: 99%
“…Obviously, using only one type of information will ignore another type of information. It has shown that combing network topology with attribute information can not only improve the quality of community detection, but also has potential to provide the semantic descriptions of communities, and help to understand the functions of communities [7][8][9][10][11].Existing methods that joint the two types of information can be roughly classified into two categories: model-based methods [12][13][14][15][16][17][18][19][20][21] and other heuristic methods [22][23][24][25][26][27]. Model-based methods are mainly on the basis of probabilistic generative models.…”
mentioning
confidence: 99%